Cultural hybridity and Australian children: speaking back to educational discourses about global citizenship. Issue 6 (1st November 2020) - Casinader, Niranjan; Manathunga, Catherine
ABSTRACT: Fluidity of cultural identity is an enduring inheritance of contemporary globalisation. One of the less-spoken consequences of this shift has been the increased pressures on young people as they navigate the transformation of their cultural identity between the new and the old. For this group, which comprises not only the children of migrants, but those born into families of multiple cultural heritages, the hybridisation of their cultural identity is occurring at a time of their lives when self-image is challenged on numerous fronts, especially at school. As scholars interested in cultural histories, geographies and pedagogies, the authors became interested in this research when they discovered mutual links with Sri Lanka and its post-1945 diaspora. This autobiographical family study draws upon micro history and life history techniques to demonstrate how the circumstances of their own families challenge macro-Australian education policy discourses about global citizenship, cultural identity and cultural understanding.